THE INTERNATIONAL LAW PERSPECTIVE ON THE CONCEPT OF PRODUCTION-SHARING AGREEMENT UNDER INDONESIA'S CUSTOMARY LAW - Rudy Haposan Siahaan1; Raja Fernandez Butar-Butar, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2017)
The legal system in Indonesia is inseparable from the history, where Indonesia was once colonized by the Dutch, so that the influence of Continental Dutch Law or Civil Law is still very strong. In addition, in international relations, Indonesia has also ratified international law that is generally affected by the Common Law legal system. Indonesia actually has had a customary law that applies in the midst of people's lives long before the formation of the unitary state of the Republic of Indonesia. These laws are generally not written. The production-sharing or profit-sharing concept applied in oil and gas law to enable the participation of foreign airlines in the management of Indonesia's oil wealth is a real example. In mining, such as PT Freeport Indonesia (America), is still practiced with 50-year-old contract of work and should end by changing its status to profit-sharing contract. The contract of work will expire in 2021 and the government will not renew it. Furthermore, the government of Indonesia issued Law No. 4 of 2009 in which the work contract regime is not known anymore but the Special Mining-Business Permit by requiring PT Freeport Indonesia to divest 51% of its shares, so that if added by 9% of the previous government’s share, it will become 60% or minority share. With some adjustments and presentation that appeal, the concept of production sharing or profit sharing is effective and is now recognized as Indonesia's contribution to the world’s oil and gas law. The concept of production sharing or profit sharing has long been recognized in customary law in Indonesia. Thus, the universal principles of international law are in fact contained in customary law which is not written but is a living law and adheres to and is upheld in the indigenous communities of Indonesia. Production-sharing contract is a method of agreement in business, used in the sector of gas, oil and mining, which has similarities with profit-sharing agreement in customary law in Indonesia because both apply the principle of apportionment and right of ownership. The application of the principle of apportionment is in accordance with the share in which greater rights go to landowners (the majority of which is in the state’s hand) and the right of ownership also in the landowners’ hand (the state). This paper is bason normative research using statute approach, conceptual approach and theory of traditional law.